Pengelolaan Bank Sampah Mandiri Secara Berkelanjutan di Kelurahan Mojosongo Surakarta - Atika Sari, Diah Apriani; Suryanto, Suryanto; Sudarwanto, Albertus Sentot; Nugraha, Setya; Utomowati, Rahning (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2022)
According to Sustainable Waste Indonesia (SWI) data, less than 10% of plastic waste is recycled and more than 50% still ends up in landfill site. The total volume of waste generated by the City of Surakarta in 2020 is 107,873 tons per year, so a waste management scheme is needed that is the joint responsibility of the government, the private sector and the community. One of the waste management schemes involving community participation is through the Waste Bank. The Waste Bank is one solution to deal with the problem of increasing waste production. The waste bank program is a collective self-subsistent waste management system with the principle of recycling. People who act as bank customers will also benefit by depositing their waste and then saving it through a waste bank and from their savings can be taken as needed. Thus, the waste bank will have a positive impact on the environment and improve economic conditions in a community. The sustainable self-subsistent waste bank management program is a solution in handling waste problems in RW 28, Mojosongo sub-district, Surakarta. The implementation of the waste bank management program in RW 28 Mojosongo Village, among others: 1) the establishment of a waste bank, 2) technical training, 3) implementation and development of the waste bank system.